Introducing engineering in K-8 settings : fostering children's powerful design ideas - Milto, Elissa, 1968-; Andrews, Chelsea; Portsmore, Merredith, 1975-; Wright, Christopher G. (New York, NY : Routledge, Taylor & Francis Group, 2025)
Introducing Engineering to K-8 Students will provide you with the tools you need to incorporate engineering design into your classroom. Rather than prescribing a specific curriculum to follow, this book will help you engage your students with hands-on, open-ended engineering design problems that can be easily integrated into your existing classroom setup. Beginning with the basics of K-8 engineering, and advancing to topics such as integrating engineering with other disciplines, documentation, and assessments, the chapters provide a how-to on creating open-ended engineering activities, design tasks, and projects that are reflective of the academic, social, emotional, developmental, and community goals of your students. An additional focus is on ways to adapt these pedagogical approaches to meet the needs of all students, representative of racially, ethnically, socioeconomically, and gender diverse populations and students who receive special education services. Case studies and practical implementation strategies are presented alongside more than fifteen lesson plans, with tips on how to modify the tasks presented in the book to work with your classroom and students. This user-centered approach will also help you create your own engineering lessons that meet your individual classroom objectives and interests, and be able to recognize and classify your students' engineering behaviors to support them in enacting their ideas. No matter your experience or comfort level, this book will be an invaluable resource for elementary and middle school science and technology teachers at all career stages who are looking to introduce engineering design to their students. Additional classroom resources can be found online at introducingengineering.org.
Keywords: Engineering -- Study and teaching (Elementary); Engineering -- Study and teaching (Middle school); Engineering design -- Study and teaching (Elementary); Engineering design -- Study and teaching (Middle school); EDUCATION / Teaching Methods & Materials / Science & Technology; EDUCATION / Elementary